Cerithiidae, Litiopidae, Modulidae and Planaxidae (Gastropoda, Cerithioidea) collected by the Marion Dufresne MD55 expedition in southeastern Brazil - Cavallari, Daniel Caracanhas; Almeida, Sérgio Mendonça; Simone, Luiz Ricardo L. (Papéis Avulsos de Zoologia, 2020)
Several deep-water mollusks collected during the Marion Dufresne MD55 expedition off SE Brazil have been studied in recent papers. The present work focuses on eight species belonging to the cerithioidean families Cerithiidae, Litiopidae, Modulidae and Planaxidae. Three species have their geographic distributions greatly expanded: Bayericerithium bayeri Petuch, 2001 from Pernambuco to Rio Grande do Norte and Ceará states (north) and to Bahia and Espírito Santo states (south), Brazilian coast; Ittibittium oryza (Mörch, 1876), from the Caribbean to the SW Atlantic; and Angiola lineata (Costa, 1778), from Trindade Island, Brazil to the Abrolhos Slope, nearly 870 km westward. Four species reported herein had their bathymetric ranges greatly expanded: Alaba incerta (d’Orbigny, 1841) from 0-40 m to 300 m; B. bayeri from 0-2 m to 120 m (live specimens); Litiopa melanostoma Rang, 1829 from 0-805 m to 1,550 m; Fossarus orbignyi Fischer, 1864 from 0-40 to 830 m (shells only).